Endogenous knowledge and agroecological resilience in Yomienkouadiokro (Ivory Coast): farming practices in the face of ecological change - N’GUESSAN , Aménan Kan Delphine Epouse BREDOU (Revue Internationale du Chercheur, 2025)
Abstract This study explores the mobilization of local agricultural knowledge in response to ecological changes in the village of Yomienkouadiokro (Gbêkê region, Ivory Coast). Based on a qualitative survey conducted in 2025 among 55 experienced farmers, it explores the mobilization of endogenous knowledge through soil management, seed selection, and climate predictions in the face of disturbances. The results reveal a peasant rationality based on careful observation of nature (birds, insects, lunar cycles), which makes it possible to anticipate the seasons, preserve soil fertility, and maintain seed diversity. However, the study indicates that this knowledge is being undermined by land pressure, reduced fallow periods, the use of herbicides, and deforestation. These dynamics exacerbate food insecurity and reinforce gender inequalities in terms of access to land. Faced with these challenges, the farming community of Yomienkouadiokro is developing strategies such as promoting plant-based pesticides (neem leaves) and preserving sacred trees. This study advocates for the integration of endogenous knowledge into climate change adaptation programs in order to promote sustainable, resilient, and socially equitable agriculture in line with local sociocultural realities.